TRANSLATING SELECTED TANKA POETRY FROM ICHIAKU NO SUNA INTO HINDI: LINGUISTIC NUANCES AND CULTURAL MEDIATION - Kumar, Pankaj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper presents a Hindi translation of selected tanka poems from Ichiaku no Suna (A Handful of Sand), the most celebrated anthology by modern Japanese poet Ishikawa Takuboku. The translation is undertaken within a multidisciplinary theoretical framework that integrates classical Indian aesthetics—particularly Anandavardhana’s Dhvani and Rasa theories—with modern Western translation models such as Eugene Nida’s dynamic equivalence and componential analysis, Peter Newmark’s semantic translation, and Lawrence Venuti’s theory of foreignization. The study investigates the complex interplay of emotion, suggestion, and cultural specificity in poetry translation, aiming to preserve the original’s emotive resonance while rendering it accessible to Hindi readers. Key challenges explored include issues of linguistic structure, poetic devices, cultural context, collocation, and gender representation. Using examples from Takuboku’s deeply personal and socially reflective poetry, the paper analyzes translation difficulties through Newmark’s classification of translation problems. It proposes solutions based on semantic feature comparison and functional equivalence. One of the study’s key innovations is the adoption of the mukt chhand (free verse) style, influenced by Hindi poet Suryakant Tripathi ‘Nirala’, to reflect the emotional and stylistic spirit of the original. Through close readings and theoretical engagement, the research underscores the importance of balancing fidelity with poetic aesthetics in cross-cultural translation. By situating Takuboku’s work within both Japanese and Hindi literary traditions, this study contributes to comparative poetics and expands the possibilities of literary translation across culturally distinct yet emotionally resonant languages.